Efektivitas Game Edukatif Counting Ball Sorting Dalam Meningkatkan Kemampuan Berhitung Anak - Haryanti, Yuriska; Anggraini, Denok Dwi (Bunayya, 2026)
Counting skills constitute an essential foundation in early childhood cognitive development and serve as an important indicator of school readiness. This study aims to analyze the effectiveness of the Counting Ball Sorting educational game in improving counting skills among children aged 4–5 years (Kindergarten Group A) at TK Darul Ulum Sumur Dalam Tamberu Agung. The counting skills assessed include recognizing number symbols, counting objects, performing one-to-one correspondence, and matching numbers with quantities. This research employed a quantitative approach using a pre-experimental design with a one group pretest–posttest model. The participants consisted of 20 children selected through total sampling. Data were analyzed using descriptive statistics and a paired sample t-test after meeting the normality assumption. The results revealed a statistically significant improvement in children’s counting skills (p < 0.05), with a very large effect size (Cohen’s d = 3.79). These findings indicate that hands-on sorting and matching activities based on quantity and color effectively stimulate children’s understanding of the relationship between number symbols and quantities. The novelty of this study lies in integrating sorting activities as a cognitive strategy that combines numeracy stimulation and fine motor coordination within a simple manipulative game design implemented in a rural early childhood education context. Practically, the results of this research imply that the use of educational games based on concrete activities can become an alternative strategy for numeracy learning that is more interactive, meaningful, and appropriate to the developmental characteristics of early childhood.